GRIK3 rs490647 is a Common Genetic Variant between Personality and Subjective Well-being in Chinese Han Population - Chuanxin Liu; Liping Zhu; Gabriel Robert; Yifeng Xu; Bo Bai; Lin An; Naixin Zhang; Zhixuan Chen; Decheng Ren; Fan Yuan; Ruixue Yuan; Yan Bi; Lei Ji; Zhenming Guo; Gaini Ma; Fei Xu; Fengping Yang; Lin He; Tao Yu; Guang He (Emerging Science Journal, 2019)
Personality and subjective well-being (SWB) have been suggested to be strongly related in previous studies. This study was intended to confirm the relationship between personality and SWB and tried to seek out the genetic variants which underlie both personality and SWB. The subjects were 890 participants from Chinese Han population. We evaluated their personality using the Big Five Inventory (BFI) and used the Satisfaction With Life Scale (SWLS) to reflect their SWB. Five single nucleotide polymorphisms (SNPs) were selected from the literature (rs1426371, rs2164273, rs322931, rs3756290, rs490647) and genotyped for genetic association study. We found negative correlations between neuroticism and SWB. On the contrary, extraversion and agreeableness were positively associated with SWB. Three SNPs (rs2164273, rs3756290, rs490647) out of the five were found to connect with personality (extraversion, neuroticism, conscientiousness and openness to experience) and rs490647 variants of GRIK3 was also associated with SWB. Individuals carrying G allele at this site were predisposed to have lower risk to be neuroticism and greater chance to be extraverted, open and satisfied with their life. In summary, our study revealed that rs490647 might be a good candidate genetic variant for personality and SWB in Chinese Han population.